Biological impacts of glyphosate on morphology, embryo biomechanics and larval behavior in zebrafish (Danio rerio). (August 2017) - Zhang, Shuhui; Xu, Jia; Kuang, Xiangyu; Li, Shibao; Li, Xiang; Chen, Dongyan; Zhao, Xin; Feng, Xizeng
Abstract: All of these days, residues of herbicides such as glyphosate are widely distributed in the environment. The ubiquitous use of glyphosate has drawn extensive attention to its toxicity as an organic pollutant. In this study, we employed larval zebrafish as an animal model to evaluate the effect of different concentrations of glyphosate on early development via morphological, biomechanics, behavioral and physiological analyses. Morphological results showed that an obvious delay occurred in the epiboly process and body length, eye and head area were reduced at concentrations higher than 10 mg/L. The expression of ntl ( no tail ) shortened and krox20 ( also known as Egr2b, early growth response 2b ) changed as the glyphosate concentration increased, but there was no change in the expression of shh (sonic hedgehog). In addition, biomechanical analysis of the elasticity of chorion indicated that treated embryos' surface tension was declined. Furthermore, a 48-h locomotion test revealed that embryonic exposure to glyphosate significantly elevated locomotor activities, which is probably attributed to motoneuronal damage. The decreased surface tension of chorion and the increased locomotive activities may contribute to the hatching rates after glyphosate treatment. Our study enriches the researches of evaluating glyphosate toxicity and probablely plays a warning role in herbicides used in farming. Graphical abstract: Highlights: High concentrations of glyphosate can induce zebrafish development delay and embryonic death. Biomechanics analysis indicates the surface tension of chorion is decreased after glyphosate exposure. Embryonic exposure to glyphosate damages embryos CaP axons and induces larval locomotor activities increased.